Montenegro : Technical Assistance Report-External Sector Statistics. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2022)
The International Monetary Fund (IMF)'s Statistics Department (STA) conducted a technical assistance (TA) mission to the Central Bank of Montenegro (CBM) for the compilation of external sector statistics (ESS) during April 28-May 13, 2021. The mission was funded by Eurostat to meet the European Union (EU)'s acquis1 from the ESS perspective. The mission focused on the compilation of quarterly international investment position (IIP),2 and assisted the CBM in preparing the Reserves Data Template (RDT) as well as in recording of financial intermediary services indirectly measured (FISIM) in balance of payments statistics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Money and Monetary Policy